Effects of the intensity, duration and muscle mass factors of isometric exercise on acute local muscle hemodynamic responses and systematic blood pressure regulation - Lin, Songmei; Sun, Pu; Huang, Liwan; Hernandez, Manuel; Yu, Hongjun; Jan, Yih-Kuen (Frontiers in Bioengineering and Biotechnology, 2024)
Isometric exercise is a non-pharmacologic intervention to improve muscle hemodynamic responses and blood pressure in humans. However, the effects of intensity, duration, and muscle mass factors of isometric exercise on local muscle hemodynamic responses and systemic blood pressure regulation have not been studied. The purpose of this study was to assess whether various modes of isometric exercise could induce various levels of muscle hemodynamic responses that are related to the blood pressure changes. Near-infrared spectroscopy was used to assess muscle hemodynamic responses after 4 isometric exercise protocols in 20 healthy adults. One-way analysis of variance (ANOVA) with repeated measures was used to assess the effect of factors of isometric exercise on oxyhemoglobin, deoxy-hemoglobin, blood volume, and oxygenation. For oxygenation, the lowest mean was recorded for the unilateral isometric handgrip exercise at 30% of MVC for 2 minutes (-0.317±0.379 M) while the highest mean was observed for the isometric wall squat (1.496 ±0.498 M, P<0.05). Additionally, both the bilateral isometric hand grip exercise at 30% MVC for 1 minute (1.340±0.711 M, P<0.05) and the unilateral isometric handgrip exercise at 20% MVC for 3 minutes (0.798±0.324 M, P<0.05) are significantly higher than 30% of MVC for 2 minutes. Blood pressure showed an inverse trend with oxygenation changes of the forearm muscle. The study indicates that the duration and muscle mass of isometric exercise are more effective on oxygenation responses and systematic blood pressure regulation, and suggests that the local muscle oxygenation factor following isometric contractions may mediate systematic blood pressure regulation.